Water Quality Mapping in the Mojorejo Sukoharjo TPA Residential Area in 2024 - Maulana, Irham Dhafin; Mifbakhuddin; Irawati, Estri (Jurnal Kesehatan, 2024)
Introduction: Mojorejo Sukoharjo TPA is located close to residential areas, namely 500 Meter and the condition of the TPA is stated to be overloaded in 2025 and the surrounding conditions are already polluted as seen from the river water which is close to the TPA. Researchers are interested in examining the condition of the water used by residents living around the landfill, whether it is polluted or not. Method: This research is an analytical observational study. This research was carried out using a brief cross-sectional research design. With the population taken in the form of 15 water samples which were close to the Mojorejo TPA and sample testing was carried out at LABKESDA Sukoharjo Regency. Results: from the results of this study, it was stated that from a total of 7 samples that had an odor or did not meet the requirements, there were 5 samples, the TDS in this research area was 193.0 mg/l - 298.0 mg/l, so the TDS met the requirements for clean water quality standards, for the water temperature in the area is 27 – 300 C so it meets the requirements, the color of the water samples in the area is clear and colorless, this makes the water meet the requirements, the pH in the research area is low and the tone is high, exceeding the clean water requirements. namely in the range of 1.25 – 13.69, for Fe levels in the research area in accordance with PERMENKES NO. 32 of 2017 was declared to meet the requirements, namely with results of 0.000 mg/l to 0.37 mg/l. Conclusion: of all the samples obtained the odor parameters did not meet the requirements, for the TDS parameters they met the requirements, the temperature parameters met the requirements, the color parameters met the requirements, the pH parameters did not meet the requirements, the iron/Fe parameters met the requirements.   Pendahuluan: TPA Mojorejo Sukoharjo berlokasi dekat dengan pemukiman penduduk yaitu 500 Meter dan kondisi TPA tersebut dinyatakan kelebihan beban pada tahun 2025 dan kondisi sekitar sudah tercemar terlihat dari air sungai yang berada dekat dengan TPA tersebut. Peneliti tertarik untuk meneliti tentang kondisi air yang digunakan oleh warga yang tinggal di sekitar TPA tersebut, apakah tercemar atau tidak. Metode: Penelitian ini merupakan penelitian observasional analitik. Penelitian ini dilakukan dengan menggunakan rancangan penelitian cross sectional singkat. Dengan populasi yang diambil berupa 15 sampel air yang berada dekat dengan TPA Mojorejo dan pengujian sampel dilakukan di LABKESDA Kabupaten Sukoharjo. Hasil : dari hasil penelitian ini dinyatakan dari total 7 sampel yang berbau atau tidak memenuhi syarat terdapat 5 sampel, TDS pada daerah penelitian ini sebesar 193,0 mg/l - 298,0 mg/l maka TDS tersebut memenuhi syarat baku mutu air bersih, untuk suhu air pada daerah tersebut 27 – 300 C maka memenuhi syarat, warna sampel air pada daerah tersebut bening dan tidak berwarna maka hal ini menjadikan air tersebut memenuhi syarat, pH pada daerah penelitian rendah dan tonusnya tinggi sehingga melebihi syarat air bersih yaitu pada kisaran 1,25 – 13,69, untuk kadar Fe pada daerah penelitian sesuai dengan PERMENKES NO. 32 Tahun 2017 dinyatakan memenuhi syarat yaitu dengan hasil 0,000 mg/l sampai dengan 0,37 mg/l. Kesimpulan: dari semua sampel yang diperoleh parameter bau tidak memenuhi syarat, untuk parameter TDS memenuhi syarat, parameter suhu memenuhi syarat, parameter warna memenuhi syarat, parameter pH tidak memenuhi syarat, dan parameter besi/Fe memenuhi syarat.